SOSIALISASI PENGEMBANGAN LAHAN PERTANIAN MENJADI AGROWISATA DI KEBUN BUAH NURSERY UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - Nasution, Nurhadida; Ainani As’ad, Octasella; Surbakti, Supriadi; Eva Yanti, Mariana (Jurnal Inovasi Pengabdian Masyarakat, 2025)
This community service activity aims to develop the potential of agricultural land into an educational tourism destination at Kebun Buah Nursery. Agricultural educational tourism is an alternative strategy in increasing the economic and educational value of agricultural land, while providing learning experiences to the community and students about fruit plant cultivation. This community service activity was carried out in Negara Beringin Village, Sinembah Tanjung Muda Hilir District, Deli Serdang Regency. Participants in this activity were 35 people from Negara Beringin Village, Sinembah Tanjung Muda Hilir District, Deli Serdang Regency. This activity was carried out through a participatory and collaborative approach with local farmers, the local community, and related stakeholders. The results of the activity showed an increase in community understanding of educational tourism potential, as well as the preparation of a design for an agricultural educational tourism area based on local potential. The community is interested in utilizing their agriculture to be processed into tourism because it can maintain plant sustainability or increase sales and from an economic perspective it can improve community welfare.